CTIM-08. A PILOT STUDY OF ABEMACICLIB WITH BEVACIZUMAB IN RECURRENT GLIOBLASTOMA PATIENTS WITH LOSS OF CDKN2A/B OR GAIN OR AMPLIFICATION OF CDK4/6. (14th November 2022) - Murillo, Jennifer; Pan, Edward; Youssef, Michael; Raslan, Omar; Maher, Elizabeth; Bachoo, Robert
Abstract: The recurrence rate for glioblastomas is essentially 100% and median overall survival (OS) for recurrent glioblastoma patients is usually poor, approximately 6-8 months from first recurrence. There is an unmet need in recurrent glioblastomas for novel therapeutic options with favorable safety profiles and potentially longer OS. PURPOSE: The goal was to assess the impact of treating recurrent Glioblastoma patients whose tumors harbor loss of CDKN2A and/or CDKN2B, and/or copy gains or amplifications of CDK4 and/or CDK6 with dual therapy Abemaciclib with Bevacizumab. METHODS: This was a single institution, pilot study (N = 10) of recurrent glioblastoma patients given the combination of Abemaciclib with Bevacizumab. Study patients received the combination of Abemaciclib at 150 mg po bid daily along with intravenous Bevacizumab at 10 mg/kg once every 2 weeks within a 28-day cycle. Staging brain MRIs with contrast were obtained every 8 weeks. Trial patients were removed from the study for significant treatment toxicities, clinical or MRI progression, patient choice, or death. RESULTS: A total of 10 patients were enrolled in the study. There were 3 patients initially enrolled that were evaluated for safety followed by the additional 7 patients meeting clinical accrual from Jan. 2020-Sept. 2021. A total of 9 patients received at least one cycle (M = 6, F = 3). Preliminary findings revealed a median PFS of 14 weeks (range 5 weeks–25 weeks) and median OS of 20 weeks (range 5-70 weeks). CONCLUSION: The combination of Abemaciclib with Bevacizumab compared to monotherapy Bevacizumab, surprisingly, had poorer outcomes. In a 2014 Bevacizumab study in recurrent glioblastomas, the median PFS was 13 weeks and OS 34.8 weeks compared to our combination therapy study of 14 weeks and 20 weeks, respectively. It is postulated that the use of Bevacizumab with Abemaciclib caused a drug-drug interaction that led to poor outcomes in our pilot study.